Overinvestment and the Operating Performance of SEO Firms - FU, Fangjian (Institutional Knowledge at Singapore Management University, 2010)
Prior studies have documented that firms' operating performance deteriorates following seasoned equity offerings (SEOs). This paper proposes and empirically tests the hypothesis that the poor performance is caused by managers' overinvestment. I show that, subsequent to the offering, SEO firms tend to invest more heavily than non-issuing control firms that are in the same industry and have enough financial slack and similar amounts of investment opportunities. More importantly, I find a negative relation between post-issue investment and operating performance, controlling for investment opportunities and pre-issue performance. The evidence supports an overinvestment interpretation as it stands in contrast to the prediction of an optimal investment model, in which firms in anticipation of decreased operating performance should invest less. Consistent with the overinvestment hypothesis, asset productivity decreases and the probability of delisting increases with excess investment. The negative effect of overinvestment is stronger in firms with relatively fewer investment opportunities.